Some Conformal Invariants from the Noncommutative Residue for Manifolds with Boundary - Ugalde, W.J. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
We review previous work of Alain Connes, and its extension by the author, on some conformal invariants obtained from the noncommutative residue on even dimensional compact manifolds without boundary. Inspired by recent work of Yong Wang, we also address possible generalizations of these conformal invariants to the setting of compact manifolds with boundary.